2014
DOI: 10.1007/s10140-014-1262-9
|View full text |Cite
|
Sign up to set email alerts
|

The utility of CT for predicting bile leaks in hepatic trauma

Abstract: The purpose of this study was to determine the efficacy of CT to predict the development of bile leaks in hepatic trauma. This HIPAA-compliant retrospective study was IRB approved and consent was waived. All patients who sustained hepatic trauma between January 1, 2006, and January 31, 2012, and who underwent CT and hepatobiliary scans during the same hospital admission were included. One hundred and thirty-two patients met the inclusion criteria. Comparison between the presence of biliary injury relative to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Although, the presence of free fluid is sensitive, it is non-specific for bile leak. In a recent study of liver lacerated patients, CT scanning showed 98% hemoperitoneum but only 25% had bile leak [12].…”
Section: Discussionmentioning
confidence: 95%
“…Although, the presence of free fluid is sensitive, it is non-specific for bile leak. In a recent study of liver lacerated patients, CT scanning showed 98% hemoperitoneum but only 25% had bile leak [12].…”
Section: Discussionmentioning
confidence: 95%
“…However, there are limitations to emergency MRCP, including lack of readily available MR imaging equipment, technologists, personnel experienced with interpreting MRCP, and higher cost (4). Therefore, HBS is the commonly used modality to diagnose biliary injury (1).…”
Section: Discussionmentioning
confidence: 99%
“…HBS can determine whether a fluid collection seen on ultrasound or CT is of biliary origin (1,2). HBS can determine the rate of leakage and can be used as a follow-up tool (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations